Improving disease management of patients with inflammatory bowel disease: the potential role of self-concordant health goals - Horvát, Barbara; Dávid, Anett; Sallay, Viola; Rafael, Beatrix; Njers, Sanela; Orbán, Kata; Molnár, Tamás; Csabai, Márta; Martos, Tamás (Frontiers in Psychology, 2023)
Inflammatory bowel diseases (IBD) are chronic gastrointestinal conditions that significantly impact a patient’s quality of life. According to previous research, the prevalence of anxiety is higher among patients with IBD compared to the general population and other chronic diseases. Focusing on patients’ self-management strategies, the key objective of this study was to test a model with hypothesized relationships between goal integration, positive and negative emotions, goal self-efficacy, and trait anxiety as the outcome variable. Based on the Self-Concordance Model (SCM) of Self-Determination Theory (SDT), goals that are integrated into the self are associated with more satisfying and enjoyable experiences and fewer negative emotions, which improves psychological functioning. Health-related goals were measured with the Personal Project Analysis technique. The State-Trait Anxiety Inventory was used to measure the level of general anxiety. Of 141 inflammatory bowel disease patients, 96 reported having a health-related goal, including 66 females (68.75%) and 30 males (31.25%). Path analysis supported that self-concordance has a moderate negative association with negative emotions and trait anxiety. Neither positive emotions nor self-efficacy significantly predicted the level of anxiety. Well-integrated health goals include an internal resource mobilization capacity, which helps patients better cope with negative emotions during self-management activities. Better negative emotional regulation can lead to lower anxiety, thus enhancing psychological functioning. The results may help design prevention and intervention programs for improving IBD patients’ coping with the disease.